PENGARUH PENDIDIKAN KESEHATAN MENGGUNAKAN MEDIA VIDEO, DEMONSTRASI, DAN LEAFLET TERHADAP PENGETAHUAN SADARI PADA REMAJA PUTERI - Nurhayati, Pipin; Nur Hartiningsih, Sri; Isnaeni, Yeni (Institut Kesehatan dan Teknologi Al Insyirah, 2023)
Every woman can get breast cancer, including teenage girls. Early detection of breast cancer can be done to determine the onset of breast cancer. Demonstrations, videos and leaflets are media that can be used to increase knowledge about early detection of breast cancer. This study aims to determine the effect of health education using video, demonstration, and leaflet methods on the conscious knowledge of adolescent girls. The design of this research is one group pre test posttest. The population used is young women in SMA Negeri 2 Banguntapan totaling 449 people. Sampling technique using consecutive sampling obtained 20 people. Test the hypothesis with the Wilcoxon test. The result is 45% of respondents have sufficient knowledge before being given health education. After being given health education, 85% of respondents have good knowledge. Wilcoxon test obtained p value 0.000 <0.05. Conclusion: There is an effect of health education using video, demonstration, and leaflet methods on the awareness of adolescent girls.